2016
DOI: 10.1088/0953-8984/29/2/025101
|View full text |Cite
|
Sign up to set email alerts
|

Proofreading of DNA polymerase: a new kinetic model with higher-order terminal effects

Abstract: The fidelity of DNA replication by DNA polymerase (DNAP) has long been an important issue in biology. While numerous experiments have revealed details of the molecular structure and working mechanism of DNAP which consists of both a polymerase site and an exonuclease (proofreading) site, there were quite a few theoretical studies on the fidelity issue. The first model which explicitly considered both sites was proposed in the 1970s and the basic idea was widely accepted by later models. However, all these mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…These considerations have been addressed in recent kinetic formalisms of growth velocity and fidelity during the real, non-equilibrium process, these models including nearest neighbor and higher-order effects 3538 . In addition, within the context of information theory and thermodynamics of DNA replication, it has been recently shown that to keep the fidelity within a given tolerance, average consumed energy E must increase with the reliability of the incorporated nucleotide according the next relation 33 (see Methods):where p error is the sequence-independent probability of error per incorporated nucleotide (or error rate) in the absence of exonucleolytic proofreading and β  = 1/ kT .…”
Section: Discussionmentioning
confidence: 99%
“…These considerations have been addressed in recent kinetic formalisms of growth velocity and fidelity during the real, non-equilibrium process, these models including nearest neighbor and higher-order effects 3538 . In addition, within the context of information theory and thermodynamics of DNA replication, it has been recently shown that to keep the fidelity within a given tolerance, average consumed energy E must increase with the reliability of the incorporated nucleotide according the next relation 33 (see Methods):where p error is the sequence-independent probability of error per incorporated nucleotide (or error rate) in the absence of exonucleolytic proofreading and β  = 1/ kT .…”
Section: Discussionmentioning
confidence: 99%
“…Its reciprocal defines the mismatch-specific fidelity which again consists of the initial discrimination and the proofreading efficiency, but the latter differs significantly from f pro defined in Sec.I, since the effective elongation rate is not but instead which includes the next-nearest neighbor effects. The same logic can be readily generalized to higher-order neighbor effects where the proof-reading efficiency will be more complicated [20, 21].…”
Section: Methodsmentioning
confidence: 99%
“…This is generally different from the F pro defined by Eq. (20). They might be approximately equal only under some conditions.…”
Section: Fig 10mentioning
confidence: 98%
See 1 more Smart Citation
“…Instead, it has to be regarded as apparently reversible like Fig.1(B2). For such schemes, Michaelis-Menten kinetics is invalid, and one should use the copolymerization theory to analyze the polymerization process, such as the steady-state copolymerization theory [5,6], the first-passage (FP) method [7] developed by us and the iterated function system (IFS) developed by P.Gaspard [8] .…”
Section: Introductionmentioning
confidence: 99%